Dynamics of soil biogeochemical gas emissions shaped by remolded aggregate sizes and carbon configurations under hydration cycles. (9th November 2017) - Ebrahimi, Ali; Or, Dani
Abstract: Changes in soil hydration status affect microbial community dynamics and shape key biogeochemical processes. Evidence suggests that local anoxic conditions may persist and support anaerobic microbial activity in soil aggregates (or in similar hot spots) long after the bulk soil becomes aerated. To facilitate systematic studies of interactions among environmental factors with biogeochemical emissions of CO2, N2 O and CH4 from soil aggregates, we remolded silt soil aggregates to different sizes and incorporated carbon at different configurations (core, mixed, no addition). Assemblies of remolded soil aggregates of three sizes (18, 12, and 6 mm) and equal volumetric proportions were embedded in sand columns at four distinct layers. The water table level in each column varied periodically while obtaining measurements of soil GHG emissions for the different aggregate carbon configurations. Experimental results illustrate that methane production required prolonged inundation and highly anoxic conditions for inducing measurable fluxes. The onset of unsaturated conditions (lowering water table) resulted in a decrease in CH4 emissions while temporarily increasing N2 O fluxes. Interestingly, N2 O fluxes were about 80% higher form aggregates with carbon placement in center (anoxic) core compared to mixed carbon within aggregates. The fluxes of CO2 were comparable for both scenarios of carbon sources. These experimental results highlight the importance of hydration dynamics in activating different GHG production and affecting various transport mechanisms about 80% of total methane emissions during lowering water table level are attributed to physical storage (rather than production), whereas CO2 emissions ( 80%) are attributed to biological activity. A biophysical model for microbial activity within soil aggregates and profiles provides a means for results interpretation and prediction of trends within natural soils under a wide range of conditions. Abstract : The study highlights the role of carbon distribution within soil aggregates on anaerobically produced GHGs, with highest N2 O emissions measured from aggregates with centered carbon source. The results quantify the temporal and spatial scales of variability in local greenhouse gas productions from soil and highlight the role of water table fluctuations (gradual vs. abrupt) as important variable in GHG emissions resembling irrigation or precipitation patterns from the scale of hours to days.